Influence of Poynting-Robertson Drag and Oblateness on Existence and Stability of Out of Plane Equilibrium Points in Spatial Elliptic Restricted Three Body Problem (Journal of Informatics and Mathematical Sciences, 2018)
This paper studies existence and stability of the out of plane equilibrium points \(L_{6,7}\) analytically and numerically in the elliptical restricted three body problem, where both the primaries are radiating oblate spheroid, incorporating the effects of Poynting-Robertson (P-R) drag of the radiating primaries as well. It is observed that consideration of PR-drag forces results in the non-zero y-coordinate of the out of plane equilibrium points. The stability of the equilibrium points is studied in presence of PR-drag forces. Also the stability is further analyzed in the case when the PR-drag forces are neglected. We have explored the existence of out of plane equilibrium points and their stability around the binary systems: Luyten-726 and Sirius.
Keywords: P-R drag; Elliptic Restricted Three Body Problem; Out of plane equilibrium points; Binary systems